The nature and forms of financial monitoring of laundering of illegal incomes and their entering into the legitimate economy - Nurmagambetov, S. Z. (Journal of Economic Research & Business Administration, 2015)
In the scientific article risk of banks’ involvement in the process of shadow economy’s money laundering exists not only on the international level, but also in Kazakhstan. Risk of banks involving is dangerous for Kazakhstan’s banking system, it prevents expansion of banks of the Republic of Kazakhstan’s activity in at the international level, also it leading to the loss of public trust. The necessity to establish an effective system for financial monitoring for managing risks of involvement of banks in the legalization of incomes of the shadow economy and the growing socio- economic threats. Risk of legalization of criminal incomes often occurs when placing money in banks, and it attracts great attention to the system of financial monitoring. Relevance of research topic also stems from the fact that owing to financial globalization of world financial markets various types and methods of financial criminal activity spread rapidly.